Directing-Group-Assisted Transition-Metal-Catalyzed Direct C–H Oxidative Annulation of Arenes with Alkynes for Facile Construction of Various Oxygen Heterocycles - Kuang, Guanghua; Liu, Guangyuan; Zhang, Xingxing; Lu, Naihao; Peng, Yiyuan; Xiao, Qiang; Zhou, Yirong (Synthesis, 2020)
The most recent advances in the construction of oxygen heterocycles by the directing-group-assisted transition-metal-catalyzed direct oxidative annulation of arenes with diverse alkynes are summarized in this review. More than 140 recent research papers and many closely related reviews are referenced in this paper. Nine different oxygen heterocycles frameworks are discussed. Several traditional transition-metal catalysts as well as some classical non-noble metals are utilized to promote the annulation. Three plausible controlling models are disclosed to clarify the excellent regioselectivity outcomes achieved in case of unsymmetrical alkyne substrates.1 Introduction2 Coumarins3 I socoumarins and Their Analogues4 2-Pyrones and Their Analogues5 Chromones and Chroman-4-ones6 Chromenes and Isochromenes7 Fused Polycyclic Oxygen Heteroaromatics8 Benzofurans, Dihydrobenzofurans, and Furans9 Phthalides and Benzofuranones10 Benzoxepines11 Conclusion
Keywords: directing group; transition-metal catalysis; C–H activation; oxidative annulation; alkyne; oxygen heterocycle